Antioxidant Activity of Passiflora edulis (Passion fruit) Seed Extracts Obtained from Maceration and Ultrasonic Assisted Extraction Method - Aktsar Roskiana Ahmad; Abd. Malik (Universitas Pakuan, 2023)
Passion (Passiflora edulis) fruit belongs to the Passifloraceae family and has high-value economics. The extraction efficiency is affected by the phytochemical’s properties of plant, the solvent and extraction method used to extract the desired compounds. The seeds of passion fruit exhibit an oil content, the valuable bioactive compound as antioxidant activity. The passion fruit seed were the waste obtained from the passion fruit syrup company in Makassar City. This study aims to determine the effect of different extraction methods on antioxidant activity of passion fruit seed extracts. The seed was macerated with methanol at room temperature for 5 days, and the ultrasonic-assisted extraction (UAE) process was performed for 30 minutes. The antioxidant capacity was measured using 2,2-diphenyl-1-picrylhydrazyl (DPPH). The results showed that the percentage yield of extract from UAE was 6.45% and the extract yield from maceration method was 5.458%. The result of antioxidant activity (IC50 value) revealed that the methanol extract obtained from UAE and maceration were 71.672 ug/mL and 144.901 ug/mL, respectively. These results indicate that the UAE method is a suitable extraction method to produce strong antioxidant activity from Passiflora seed extract.